(untitled) (Research, Society and Development, 2022)
Since it was decreed in December 2019, the COVID-19 pandemic has taken on enormous proportions. In this context in which all aspects of human life have been affected, it is important, within the scope of women’s health, to understand the impacts of COVID-19 on the menstrual cycle, given its importance in women’s lives. The objective of this work was to search for studies capable of describing the changes in the menstrual cycle observed due to COVID-19 and the pathophysiology that is linked to these changes, as well as their consequences. A normal menstrual cycle is an indicator of good health, whereas disturbances in the menstrual cycle can indicate underlying conditions. Different types of cells found in the gonads show expression of angiotensin converting enzyme 2 (ACE2) and transmembrane serine protease subtype 2 (TMPRSS2), which provide key entry pathways for the SARS-CoV-2 virus into the cell. In addition, the systemic biological effects of COVID-19 infection can influence the hypothalamic-pituitary-adrenal axis, increasing stress and, consequently, cortisol, exerting a global effect on the functioning of the body. The systematic review demonstrated that COVID-19 reversibly influences the increase or decrease in cycle length, menstrual irregularity, increased menstrual flow, intermenstrual spotting and more intense symptoms in the premenstrual period, such as abdominal pain and increased premenstrual tension. In addition, the impact of the pandemic on mental health and sexual behavior may affect human reproduction, thus, the pandemic was associated with a decline in sexual satisfaction, lower libido and lower sexual frequency.